Characterization of an H2/O2 PEMFC Short‐Stack Performance Aimed to Health‐State Monitoring and Diagnosis1. Issue 3 (13th November 2017) - Petrone, R.; Vitagliano, C.; Péra, M.‐C.; Chamagne, D.; Sorrentino, M.
Abstract: Proton exchange membrane fuel cell (PEMFC) is one of the most promising technologies in energy conversion. Nevertheless, improper operating conditions can severely affect the fuel cell (FC) lifespan. It is a matter of fact, that several degradation mechanisms could take place inside the cell in case of abnormal operating conditions. Among these, improper water managements, fuel quality and starvation conditions can show critical effects on PEMFC performance. Furthermore, if the exposure time to these faulty conditions resulted quite long, irreversible degradations and system ageing would occur. This work aims to investigate the impact of both improper water managements and reactants starvation conditions on H2 /O2 PEMFC short‐stacks performance. To this purpose, the experimental activity performed to characterize the stack health‐state both in normal and abnormal conditions is presented. Particular attention is dedicated to the effects caused by improper conditions on stack electrochemical impedance spectroscopy (EIS) measurements' variations. Depending on the faulty conditions, the experimental results are then analyzed for health‐state monitoring and diagnosis purposes.